An evaluation of the efficacy and value of CVT-301 for the treatment of Parkinson's disease. (24th May 2021) - Stocchi, Fabrizio; Vacca, Laura; Grassi, Andrea; Torti, Margherita
ABSTRACT: Introduction : Levodopa is the most effective drug in the treatment of Parkinson's disease, but its chronic treatment is linked to the occurrence of motor complications with fluctuations of motor performance and dyskinesia. Unpredictable OFF episodes can be severe and disabling and current rescue medications cannot always be used safely. Rescue therapy is characterized by a rapid and predictable ON response and the safety profile of levodopa will represent a major advantage for patients affected by unresponsive OFF episodes. Areas covered : CVT-301 is a new inhaled formulation of LD recently developed as a self-administered treatment for OFF periods. Herein, the pharmacodynamic and pharmacokinetic properties, efficacy, and safety of CVT-301 are reviewed. Expert opinion : CVT-301 may offer several potential advantages including increased systemic bioavailability through pulmonary absorption, rapid onset of action, avoidance of first-pass drug metabolism, and less plasma level variability. It should be noted that the delivery device used has been described as relatively simple to use, but the few steps required to prepare and self-administer the dose can be challenging for PD patients during their OFF state. Additionally, resolution of an OFF episode requires the administration of two capsules of CVT-301, which further complicates the use of the device.